Study on the Influencing Factors of Chinese Young Volunteers' Sustainable Participation in Environmental Service - Haiyan Wang, Nianyou Leng, Wanfang Huang (Forest Chemicals Review, 2022)
Young volunteers are an important group of public participation in environmental governance. However, their activities lack sustainability. From the Personal and Environment Interact Perspectives, the research divides the Volunteer process into three stages: Initial motivation stage, Volunteer process and Volunteer reflection, and extracts six factors that affect the sustainability of Young Volunteers' environmental protection Volunteer which are Pro-social, Initial Motivation, Job Engagement, Job Satisfaction, Self-Efficacy and Volunteer Identity. A structural equation model is constructed. Through investigating 588 college young Volunteer, the relationship between influencing factors was verified by structural equation model (SEM). The results reveal that the sustainable process ofyoung Volunteer' behavior is a process in which individuals and environment interact and gradually match to achieve the same.